2019
DOI: 10.3892/ijo.2019.4707
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA PLAC2 activated by H3K27 acetylation promotes cell proliferation and invasion via the activation of Wnt/β‑catenin pathway in oral squamous cell carcinoma

Abstract: As a new group of important effector molecules involved in multiple cancer types, including breast cancer, lung cancer and oral squamous cell carcinoma, long noncoding RNAs (lncRNAs) have attracted considerable attention recently. However, the underlying cause that induces the dysregulated lncRNAs in cancer remains poorly understood. In the present study, the regulatory model of the lncRNA placenta-specific protein 2 (PLAC2) upregulation in oral squamous cell carcinoma (OSCC) was investigated and its biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 46 publications
2
69
0
1
Order By: Relevance
“…The elevated expression of PLAC2 in tongue carcinoma cells resulted from the enrichment of its promoter region in H3K27 acetylation, which was dependent on CBP acetyltransferase activity. PLAC2 knockdown also diminished cell proliferation and migration [83]. The overexpression of UCA1 in laryngeal cancer cells was associated with reduced GSK-3β phosphorylation and elevated β-catenin level.…”
Section: The Role Of Epigenetic Mechanisms In Wnt/β-catenin Pathway Amentioning
confidence: 88%
See 1 more Smart Citation
“…The elevated expression of PLAC2 in tongue carcinoma cells resulted from the enrichment of its promoter region in H3K27 acetylation, which was dependent on CBP acetyltransferase activity. PLAC2 knockdown also diminished cell proliferation and migration [83]. The overexpression of UCA1 in laryngeal cancer cells was associated with reduced GSK-3β phosphorylation and elevated β-catenin level.…”
Section: The Role Of Epigenetic Mechanisms In Wnt/β-catenin Pathway Amentioning
confidence: 88%
“…Moreover, several long non-coding RNA molecules were also implicated in the regulation of Wnt signaling. The upregulation of MINCR, PLAC2 and UCA1 was frequently observed in head and neck cancers, and functionally, it promoted malignant progression by the activation of Wnt/β-catenin pathway [82][83][84]. The level of MINCR expression correlated with lymph node metastasis and shorter survival of OSCC patients.…”
Section: The Role Of Epigenetic Mechanisms In Wnt/β-catenin Pathway Amentioning
confidence: 91%
“…Hypoxia is one of the important hallmarks of tumor microenvironment. Increasing studies have revealed that tumor hypoxia is closely related to the progression of cancer, such as tumor metastasis, recurrence and drug resistance [25][26][27][28]. It has been con rmed that hypoxia in vivo is associated with poor prognosis and high mortality in ovarian cancer patients, and involved in ovarian cancer cell proliferation [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The upregulated EP300/CBP mutations may attenuate differentiation to enable the establishment of HNSCC cell cultures (Martin et al, ). H3K27ac enrichment at the promoter region of long non‐coding RNA placenta‐specific protein 2 (PLAC2) gene is shown in OSCC, while CBP depletion reduced H3K27ac and PLAC2 levels (Chen et al, ). ERK1/2 phosphorylation suppressed by melatonin reduced p300/CBP level, decreased histone acetylation, then dampened matrix metalloproteinase‐9 transcription, and decreased cell migration (Yeh et al, ).…”
Section: Histone Modifications In Osccmentioning
confidence: 99%